Fabrication Of 3d Porous Beta Tricalcium Phosphate Bone Scaffold Coated By Oly(Vinyl Alcohol) And Poly(Lactic Acid)_ - Wong, Wai Yee (2017)
The interconnected porous β-TCP scaffold was produced via polyurethane (PU) foam replica method. PVA and/or PLA were coated on the scaffold to enhance the compressive strength. The first part of this study was to optimise the internal architecture of β-TCP scaffold with minimal defect before biopolymer coating. Optimum macro- and microporosity in β-TCP scaffold were produced by slurry with ratio 10g:8ml of powder to water and addition of 2 wt. % of PVA and PEG and sintered at 1250°C for 2 hours. The optimum scaffold had 95.3% of porosity with unblock macropore, minimum crack and regular thickness of strut. In the second part, during biopolymer coating, single layer coating with higher PVA concentration had macropores blockage, while lower PVA concentration coating showed uncoated at interior of the scaffold. Bi-layer coating with PLA was to compensate the uncoated interior region in lower PVA concentration coated sample. In terms of mechanical property, compressive strength of the coated scaffold increased with the coated weight percentage of biopolymer. Polymer stretched at the crack opening showed crack bridging mechanism, which toughened the brittle β-TCP scaffold. Scaffold bi-layer coated with 3 wt. % of PVA and subsequently 5 wt. % PLA (V3_L5) had the highest compressive strength (83.7 kPa) with no macropore blocking by biopolymer. In terms of bioactivity, β-TCP without biopolymer coating took 2 weeks to form apatite but V3_L5 took 4 weeks after immersion in SBF. This showed that coating with hydrophobic PLA delayed the time of apatite formation.